Efficacy of Biofield Therapies in alleviating pain and reducing symptoms associated with mental disorders: a systematic review and meta-analysis - Sá, Rick; Quitério, Robison José [UNESP]; Pignataro Neto, G (Springer Nature, 2025)
Background and purpose: To evaluate the effectiveness of Biofield Therapies (BTs) in alleviating pain and mitigating symptoms associated with mental disorders (SAMD), with particular emphasis on comparing outcomes between touch-based and non-touch interventions. Methods: A systematic review and meta-analysis were conducted following the PRISMA 2020 guidelines. Searches were performed in PubMed, Scopus, and CINAHL, supplemented by a manual search in Google Scholar. A total of 28 randomized controlled trials (RCTs) published between 2003 and 2023 were included, assessing the effects of BTs such as Reiki, Therapeutic Touch, Healing Touch, and External Qigong. Two independent reviewers conducted screening and data extraction. Effect sizes (ES) were calculated using random-effects models, and a structured narrative synthesis was incorporated to address heterogeneity. Results: BTs demonstrated a moderate pooled effect on pain (ES = 0.784; 95% CI: 0.094 to 1.475; p = 0.030) and a mild to moderate effect on SAMD (ES = 0.326; 95% CI: 0.162 to 0.491; p < 0.001), although both analyses revealed substantial heterogeneity. A key finding was that touchbased interventions yielded a larger mean effect size (ES = 0.830) and significantly more consistent outcomes for pain (Coefficient of Variation, CV = 0.936) compared to non-touch therapies (ES = 0.680; CV = 1.327). Within the SAMD group, effects varied by symptom; anxiety and stress showed more favorable trends, while results for depression were inconsistent. No statistically significant predictors of effect size were identified in ANCOVA models for either group. Quality assessment indicated that most included studies were of moderate methodological rigor. Conclusion: Preliminary evidence suggests that BTs, particularly touch-based modalities, may offer beneficial and more consistent effects for chronic pain. BTs may also help manage certain psychological symptoms, especially anxiety and stress. However, due to significant heterogeneity in study designs and populations, these findings should be interpreted with caution. BTs may be explored as complementary approaches in integrative care, but further high-quality, standardized trials are needed to establish efficacy and guide clinical recommendations.